Standard of assessing the moral element in intentional and unintentional crimes - Rashed Abdel-Hamza, . Assistant Professor Dr. Mustafa (The college of law and political science journal, 2023)
The moral element of crime is a psychological force that creates and control,and is represented in the free, aware, and chosen will that is directed in a way thatcontradicts the speech of the legislator, or underestimates that speech. Violationof the duties of caution and caution, then we are in the process of an unintentionalmistake.7KHFULWHULRQIRUPHDVXULQJWKHIXOÀOOPHQWRIWKHPRUDOHOHPHQWLQWKHLQWHQWLRQDOcrime, i.e., the achievement of the criminal intent, is determined by the externalmanifestations that would reveal and reveal it. She is convinced of the existence ofFULPLQDOLQWHQWEXWVKHVLPSOLÀHVKHUFRQWURODQGDVNVKHUZKDWVKHLVFRQYLQFHGRIthe existence of criminal intent or not, that is, what is the evidence for the statementthat criminal intent has been achieved and what kind of manifestations indicateit, and from here it must be distinguished between what is subject to control andwhat is not subject and is considered within the discretionary powers of the court.As for the criterion for estimating the moral element in a non-intentional crime, i.e.